PENINGKATAN HASIL BELAJAR TARI DENGAN MENGGUNAKAN MEDIA CHART DI SMP NEGERI 4 PARIAMAN - Arviani, Yohana; Astuti, Fuji; Mansyur, Herlinda (SENDRATASIK UNP, 2019)
AbstractThis article aims to reveal and explain about how teachers interact with students and improve learning outcomes of students in learning the art of using the media Charts in SMP Negeri 4 Pariaman. This type of research this is a class action Research (PTK). The research was carried out in 2 cycle i.e. the cycle I and cycle II. The instruments used in this research is the written tests (cognitive) and test skills (psychomotor). The techniques used in data collection is the observation, knowledge (cognitive) tests and keterampilam tests (psychomotor). Technique of data analysis is carried out based on the activity of learning, student learning outcomes and assessment criteria. The results showed that the use of media art learning culture in chart in particular dance in Class VII. 4 SMP Negeri 4 Pariaman can improve the results of the study and was able to make student learning was directly involved in the practice of dance. On cycle I have not found an increase in student learning outcomes are significant but in cycle II by using the media, learners are more focused and serious in following the instruction. This is evident by the presence of learning outcomes grade VII. 4 on cycle I student learning outcomes the overall cognitive and psychomotor 62.95 and on student learning outcomes the overall cycle of psychomotor and cognitive 81.43. So there has been an increase in the results of learning the art of dance by using media chart and targets on want has been successful.Keywords: study results of dance, chart media